IMPLEMENTASI BUKU III KUHPERDATA TENTANG PERIKATAN PADA PERJANJIAN KERJASAMA ANTARA PT. BANK RAKYAT INDONESIA (PERSERO) TBK, DENGAN AGEN BRILINK. (STUDI PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK, UNIT STABAT) - TRI SUCI RIYANTI (Ilmu Hukum Prima (IHP), 2022)
Through Financial Service Authority (henceforth referred to as OJK), Indonesian Government, creates Branchless Banking to improve financial service and products. PT. Bank rakyat Indonesia (henceforth to as BRI) Tbk, launches BRILink and is bound in a cooperation agreement with BRILink agents to serve banking transactions for society. Some problems are found concerning implementation of the agreement such as imbalanced status between both parties’ causing obstacles in term of both parties’ right and obligation. These obstacles are encountered during the implementation of the agreement between BRI and BRILink agents, particularly in the working area of BRI Unit Stabat. This jurnal analyzes the implementation of principle of balance in the freedom to make agreement as well as all parties’ right, obligations and liabilities in the event of violations and the encounter of abstacles and solutions for them in the implementation of the agreement between BRI and BRILink agents. The results of this research demonstrate that the principle of balance in the cooperation agreement between PT. BRI and BRILink agents has to be grounded on the principle of good faith in order to create mutually beneficial relationship for both parties because their status in this agreement is factually imbalenced if assesed from power, psychological, and economical sides. All parties in this agreement have rights, obligations, and liabilities specified in the clauses that shall be implemented; and, in the event of a default, they are imposed by the sanctions in line with the contents of the agreement and the prevailing laws and regulations. Consensus meeting shall be taken precedence over other method to settle any obstacles encountered during the implementation of this agreement such as transaction failure, transaction target, profit share, and force majeure.